Studies on Crude Bark Drug - Holoptelea Integrifolia (Roxb.) Planch. - Bhuktar3, M. A. Kare1*, A. S. Dhabe2; A. S. (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Holoptelea integrifolia is belongs to family Ulmaceae. It is known as Putigandha, Chirbilva, Putikaranjah, Kanjo, Chiramil, Papri, Tapasimara, Chirabilwa, Avil, Aval, Baval, Vavala, Chirbid,Ã‚Â Avil Pattai,Ã‚Â Nemalinara, Tapazi and Indian elm tree.Ã‚Â The bark is reported to be used for treating inflammation, dyspepsia, flattulence, colic, helminthiasis, vomiting, skin-diseases, leprosy, diabetes and rheumatism. It is bitter, astringent, thermogenic and also used as anti-inflammatory, digestive, carminative, laxative, depurative, anthelmintic and repulsive. The quality of the bark which available in the form of pieces or fine powder in market is doubtful. Therefore attempts were made to standardize the bark by Morphology, Anatomy, and Maceration. By applying above parameter in the combination, the bark of Holoptelea integrifolia (Roxb.) Planch. can be standardized. Ã‚Â